Small mammal remains recovered from two archaeological sites in the middle and lower Negro River valley (Late Holocene, Argentina). Taphonomic issues and paleoenvironmental implications - Fernández, Fernando Julián (2011)
This paper presents the results of a taphonomic and paleoenvironmental analysis of small mammal remains recovered from the Negro Muerto and Angostura 1 archaeological sites. These sites (ca. 0.5 and 0.95 ka BP, respectively), are located in the middle and lower Negro River valley in northern Patagonia, Argentina. Based upon the presence of several types of evidence (cut marks, bone tools, and thermal alteration), it is proposed that Holochilus brasiliensis and cavies were acumulated by humans. At the Angostura 1 site, some remains also show evidence of having been generated by carnivores (digestion, breakage patterns, and relative skeletal element abundances). This indicates that carnivores (e.g., Puma concolor) could have contributed to the formation of the small mammal assemblages. Other small mammal species recovered at both sites (e.g., Galea leucoblephara, Microcavia australis, Akodon molinae, and Graomys griseoflavus) suggest semi-desert environmental conditions, similar to those found today. The presence of Reithrodon auritus and Oligoryzomys sp. indicate the development of open herbaceous steppe environments in proximity to bodies of water. However, the discovery of H. brasiliensis at both sites, an orizomyine of amphibious habitats and subtropical origin, and which is now absent in the area, suggests warmer and wetter conditions during this period.